High-functioning autism and second language development:A case study - Barletta, Norma Patricia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
Children with autism experience difficulties to develop their first language. Learning a second language (L2) can imply additional challenges even if immersed in a second language environment. The objective of this case study is to describe some of the features of the development of English as L2 in a six-year old child with high-functioning autism recently arrived in the US. The objective is to compare the process with that of typically developing children. Data were obtained from observations of tutorial sessions, which were recorded, transcribed and analyzed following Vygotsky´s dialectical method, in which learning is seen as a dynamic and complex process. The analysis shows that though the child experiences most phases as typically developing children do, some of the autistic features represent a challenge for L2 learning. However, given a permanent support on a one-to-one basis, some of these features can become an advantage for L2 learning.